2023
DOI: 10.1038/s41467-023-37727-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCL16 and STAT1 augments immune checkpoint blockade therapy in triple-negative breast cancer

Abstract: Chemotherapy prior to immune checkpoint blockade (ICB) treatment appears to improve ICB efficacy but resistance to ICB remains a clinical challenge and is attributed to highly plastic myeloid cells associating with the tumor immune microenvironment (TIME). Here we show by CITE-seq single-cell transcriptomic and trajectory analyses that neoadjuvant low-dose metronomic chemotherapy (MCT) leads to a characteristic co-evolution of divergent myeloid cell subsets in female triple-negative breast cancer (TNBC). Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Indeed, our study showed that CXCR6 + KO T cells are less adherent to tumor-associated myeloid cells and are more functional when directly injected into tumor tissue. This finding is consistent with some emerging data examining the blockade of CXCL16 in breast cancer ( 51 ). In this study, the authors found that blocking CXCL16 prevented CD8 + T-cell infiltration into tumors and decreased PD-1 expression, which was consistent with our observations from our knockout models and adoptive transfer experiments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, our study showed that CXCR6 + KO T cells are less adherent to tumor-associated myeloid cells and are more functional when directly injected into tumor tissue. This finding is consistent with some emerging data examining the blockade of CXCL16 in breast cancer ( 51 ). In this study, the authors found that blocking CXCL16 prevented CD8 + T-cell infiltration into tumors and decreased PD-1 expression, which was consistent with our observations from our knockout models and adoptive transfer experiments.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the authors found that blocking CXCL16 prevented CD8 + T-cell infiltration into tumors and decreased PD-1 expression, which was consistent with our observations from our knockout models and adoptive transfer experiments. This group also demonstrated that the combination of PD1 and CXCL16 blockade led to increases in CD8 + T-cell infiltration in tumors, resulting in the promotion of antitumor immunity ( 51 ). These findings are also consistent with our data showing enhanced antitumor immunity in CXCR6 KO mice treated with anti-PD1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary messengers such as cyclic adenosine monophosphate (cAMP) and Ca 2+ play a role in the following signalling events, and their variation depends on the specific alpha subunit type. 80,81 Notably, lactate is capable of signalling through GPR81 and GPR132, both of which are sensitive to protons. 82 GPR81 is detected in different tumours obtained from patients and cancer cell lines.…”
Section: Lactate Sensing Shuttling and Signallingmentioning
confidence: 99%
“…Upon the binding of an agonist, the G protein‐coupled receptor (GPCR) alpha subunit undergoes a GDP–GTP exchange. Secondary messengers such as cyclic adenosine monophosphate (cAMP) and Ca 2+ play a role in the following signalling events, and their variation depends on the specific alpha subunit type 80,81 . Notably, lactate is capable of signalling through GPR81 and GPR132, both of which are sensitive to protons 82 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fludarabine (F-ara-A; NSC 118218) is a DNA synthesis inhibitor and a fluorinated purine analogue with antitumor activity towards lymphoproliferative malignancies, which can inhibit the activation of STAT1 and STAT1dependent gene transcription induced by cytokines. There have been more than thirty studies of fludarabine over the past few years [61,62]. The docking models in Figure 8C,D demonstrate that these two drugs can target the TF EPAS1.…”
Section: Five Compounds Were Identified To Target the Tf Epas1mentioning
confidence: 99%